Features of business organization on the Internet - Kosenko , Alisa; Vanina , Yana (Theory and Practice of Public Administration, 2019)
The paper considers the issues related of business organization in the Internet are considered. The theoretical and practical aspects of  Іnternet business under the product markets globalization, internationalization and standardization of marketing management activities are researched, the essence, specificity and major performances of e-business’ tools and effective promotion of internet projects in virtual marketplace are analyzed. The analysis of the current state of Internet commerce of goods is carried out, the features and certain aspects of commodity Internet trade in the international dimension at the present stage are revealed. The modern approaches to the study of Internet commerce are analyzed. The development of electronic commerce in Ukraine.Modern society is inherent in the broad implementation of information technologies and computer communications in all areas of human activity. Given these conditions, the role of Internet technologies, whose implementation in the marketing activities of enterprises allows the latter to adapt to current market conditions and increase company’s competitiveness and efficiency of operation, significantly escalates. The Internet today helps to conduct business, meeting information needs and creating effective system of business relationship with customers, as well as with all elements of the business environment.The aforementioned statement actualizes the comprehensive study of the conceptual foundations of Internet marketing and its tools, the role of the Internet in globalization of business, scientific and practical importance.The use of the Internet brings new opportunities and advertisements advantages over marketing based on traditional methods and the classic marketing mix. First and foremost, there are new tools for marketing campaigns. There is a combination traditional marketing methods and new information technologies.Individual interaction. The global network is like a new communication environment, and so on a market with tens of millions of potential customers with a fairly high income. The emergence and development of the Internet, the improvement of information technology and systems themes and standards of interaction led to the creation of a new trend in the modern business, e-business, being the most important component of e-commerce. It allows companies more deeply respond to suppliers and respond more quickly to customer requests call.